Early Childhood Tahfizh Education: Optimization the Aspects of Children's Development and Religious Soul of Children in the Golden Age - Syahri Ramadhan; Nelia Guswanti; Evi Rahayu; Zalisman Zalisman; Yundri Akhyar (STAI Hubbulwathan Duri, 2022)
This study aims to describe tahfidz education in early childhood in terms of the perspective of the development and religious spirit of children during the golden age at the Markaz Tahfizh Balita (MARTABA) Al-Makki Pekanbaru. This type of research is qualitative research with a Case Study model. The informants of this research were teachers and students at MARTABA Al-Makki Pekanbaru. The data collection techniques use in-depth interviews (depth interviews) and observation. While the data analysis technique is done by data reduction, data display, and verification. In general, tahfizd learning activities are to form good habits from an early age that can form a religious spirit and stimulate developmental aspects in children. The tahfizd learning program at MARATABA Al-Makki Pekanbaru has facilitated aspects of early childhood development which include; aspects of internalizing moral and religious values, aspects of gross motor development, and aspects of fine motor development, aspects of language development, aspects of cognitive development, and aspects of social-emotional development. In addition to the aspects of psychological development above, the learning program also pays attention to adequate nutritional intake to stimulate children's development. Tahfizh learning is also able to optimize the development of children's religious spirit from an early age. For this reason, tahfidz learning activities for early childhood at MARTABA Al-Makki Pekanbaru can be an example of organizing a tahfidz program for early childhood.